Operational excellence proposal model on logistics management: A case study in an automotive industry - Silva, Anderson J. [UNESP]; Tramarico, Claudemir L. [UNESP]; Marins, Fernando A. S. [UNESP] (My University, 2021)
The logistics sector of automotive companies often has operational deficiencies with impact to develop strategic and competitive advantages for the organization. The logistic sector has evolved over time and has been strengthened from globalization and technological development. This sector has been looking for improvements due to the importance of the operation for the production process and to raise the standard of operational efficiency. The research was limited to an automotive company operating in southeastern of Brazil, on Taubaté city, in order to identify potential problems and propose improvement on company strategy. The purpose of this paper is mapping of all activities of the logistics process in an automotive industry. The methodological procedure was the single case study as a viable methodology for logistic management. The main contribution of this paper is to provide a proposal model for new strategies to improve logistics management and to achieve operational excellence.
Keywords: Automotive Industry; Logistics; Operational Excellence; Strategy